Caregiver Needs Assessment in Primary Care: Views of Clinicians, Staff, Patients, and Caregivers - Riffin, Catherine (J Am Geriatr Soc, 2020)
OBJECTIVES: To understand current practices, challenges, and opportunities for a systematic assessment of family caregivers’ needs and risks in primary care. DESIGN: Qualitative study consisting of in-depth semi-structured interviews. SETTING: Four primary care practices located in urban and rural settings. PARTICIPANTS: Primary care clinicians, staff, and administrators (N = 30), as well as older adult patients and family caregivers (N = 40), recruited using purposive and maximum variation sampling. MEASUREMENTS: Current experiences, challenges, and opportunities for integrating standardized caregiver assessment into primary care delivery. Interviews were audio-recorded and transcribed; transcripts were analyzed using the constant comparative method of data analysis. RESULTS: Participating clinicians had been in practice for an average of 12.8 years (range = 1–36 y). Patients had a mean age of 84.0 years (standard deviation [SD] = 9.7); caregivers had a mean age of 67.0 years (SD = 9.3). There was wide variability in current practices for identifying caregivers’ needs and risks, encompassing direct and indirect approaches, when such issues are considered. Participants posited that integrating standardized caregiver assessment into primary care delivery could help improve patient care, enhance clinician-caregiver communication, and validate caregivers’ efforts. Barriers to assessment included insufficient time and reimbursement, liability concerns, lack of awareness of community resources, and concerns about patient autonomy. To facilitate future uptake of caregiver assessment, participants recommended brief self-administered assessment tools and post-screen discussions with practice staff. CONCLUSION: Identification of caregivers’ needs and risks in primary care is highly variable. Integration of standardized caregiver assessment into practice requires coordinated changes to policy, revision of practice workflows, and an interdisciplinary approach to the development of appropriate assessment tools.